Rapid Shifts in Relative Abundance Obscure Temporal Diversity Changes in a Metacommunity - William Godsoe; Warwick J. Allen; Lauren P. Waller; Barbara I. P. Barratt; Sarah P. Flanagan; Zachary H. Marion; Jason M. Tylianakis; Elena Moltchanova; Ian A. Dickie (Ecology and Evolution, 2025)
ABSTRACT Changes in biodiversity reflect processes acting at multiple spatial scales, from local to global, among habitats and within communities. This complexity makes it difficult to measure mechanisms that have traditionally interested ecologists, such as environmental filters. To resolve this, we propose an approach to partition temporal changes in biodiversity into contributions from selection at multiple scales. We applied this approach to study changes in the biodiversity of invertebrate herbivores from a large‐scale, plant community experiment. Though the experiment was designed to foster distinct insect communities due to differences in host plants, our approach showed that selection among these treatments was a negligible facet of diversity change. These effects were swamped by rapid changes in relative abundances of aphids due to both immigration and selection across the metacommunity. More broadly, our work highlights how total change in biodiversity across a biogeographic region can be partitioned into logically distinct mechanisms.